The apparent metabolisable energy requirement of Sansui ducks from hatch to 21 days of age - Y.L. Feng; G.T. Dai; M.J. Li; J.H. Wu; J.E. Xu; X. Han (Journal of Applied Animal Nutrition)
A dose-response experiment was conducted to estimate optimal dietary apparent metabolisable energy requirement (AME) in Sansui ducks (Sansui Sheldrake duck) from hatch to 21 days of age. Three hundred thirty-six one-day-old male Sansui ducks were randomly assigned to six experimental treatments, each consisting of seven replicate pens with eight birds per pen. Birds were fed diets containing either 10.92, 11.38, 11.8, 12.26, 12.68 and 13.14 MJ AME/kg, respectively. At 21 d of age, the body weight, weight gain, feed intake, protein intake, energy intake and feed conversion ratio of ducklings from each pen were measured. Increasing AME content from 10.92 MJ/kg to 13.14 MJ/kg significantly improved body weight, weight gain, feed intake, feed conversion ratio and crude protein intake (P<0.05). No significant changes in energy intake were found among treatments (P>0.05). Based on broken-line regression analysis, the AME requirement of male Sansui ducks from hatch to 21 d of age was 11.49 and 11.59 MJ/kg for maximum body weight and best feed conversion ratio, respectively.